Customary Law and Islamic Law Existence in the Reform of National Criminal Law - Rossa Ilma Silfiah; Suwardi, Suwardi; Khoirul Huda; Indratirini, Indratirini (Dinasti Research, 2024)
The existence of criminal law is a necessity for a nation to regulate the lives of its citizens. Indonesia is a constitutional state that has experienced a long legal history. Prior to the independence, the Indonesian people were familiar with the customary laws and religious laws of each resident. Customary Law and Islamic Law were jointly obeyed by the people at that time. As a living law, both are the solution for society in facing legal disputes. It is not surprising, then, that besides Positive Law, which is known to originate from Western/Colonial Law, Islamic Law and Customary Law have a higher bargaining position. So that in the establishment of National Law, Islamic Law and Customary Law become material sources for the establishment of a positive law. The formation of national law, therefore, including criminal law, really needs the contribution of Islamic law, in addition to customary and western law. The history of the development of criminal law in Indonesia is colored by Islamic values, because the socialization process of Islamic law is integrated with the development of customs in resolving criminal cases.